Anuario 2024 del Centro de Investigación de Agroindustria (CIA) - Instituto Nacional de Tecnología Agropecuaria (INTA). Centro de Investigación de Agroindustria (Centro de Investigación de Agroindustria, INTA, 2025)
We are the AGROINDUSTRY RESEARCH CENTER (CIA), comprised of two institutes: the Rural Engineering Institute (IIR) and the Food Technology Institute (ITA), and we are part of the NATIONAL AGRICULTURAL RESEARCH CENTER (CNIA) of INTA (National Institute of Agricultural Technology). Our mission is to contribute to innovation and the sustainable development of the Agrifood and Bioindustrial System (SAB) through participatory processes, scientific research, and high-quality technological development. Our fundamental pillars of work include creating a work environment that prioritizes people's well-being, promoting training, inclusion, and equity. We develop human talent, generate and manage knowledge to anticipate demands and respond to the needs of the SAB, focusing on the comprehensive valorization of agrifoods and the design and adaptation of technologies that improve the efficiency and sustainability of agroindustrial chains. We promote responsible communication focused on highlighting and sharing with society the knowledge, innovations, and actions developed by the CIA, consolidating it as a benchmark in the scientific and technological field and in the SAB, positioning the products, services, developments, and innovations generated by the CIA in the sector and in the public sphere, strengthening local, regional, national, and international ties. We collaborate closely with the public and private sectors, creating synergies that promote innovation as a sociotechnical process, integrating institutional and extra-institutional capacities into a strategic planning process with a forward-looking and territorial vision. Our projects generate value for our users and institutions and positively impact society by promoting job creation, the development of new skills, and the efficient use of resources. Through this document, we intend to report on the activities carried out and the products obtained, as well as the resources available during 2024 related to the strategic components: research and development, extension and transfer, technology linkage, institutional relations, information, and communication. The CIA works with open doors, and any concerns can be channeled through our communication channels.